Distributional and labour supply effects of tax-benefit policies - Kalíšková, Klára; Kopa, Miloš; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
Tax and benefit systems play a crucial role in redistributing incomes, shaping income inequality, and influencing labor supply dynamics. This thesis addresses the complex interplay between tax-benefit policies, their impact on equity and efficiency, and the unintended consequences they sometimes bring. The thesis comprises two main lines of research. Firstly, it examines the distributional impacts of tax and benefit policies, analyzing the tax burden across income groups, the redistributive effects of the benefit system, and the impact on income inequality and poverty. Secondly, it investigates the labor supply effects of tax-benefit policies, including an analysis of female labor supply responsiveness across European countries and the effects of family taxation reforms on married couples' labor supply. Additionally, this thesis explores the unintended consequences of benefit policies, as demonstrated by the study on parental allowance reforms and their impact on maternal unemployment. The use of empirical evidence contributes to a deeper understanding of the consequences of tax-benefit policies, which can inform policymakers' decisions and guide future research in this field.
Vedoucí práce
Habilitační práce (doc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet